#### Answer

\[{h^,}\,\left( 3 \right) = 77\]

#### Work Step by Step

\[\begin{gathered}
Let\,\,h\,\left( x \right) = f\,\left( x \right)g\,\left( x \right) \hfill \\
Find\,\,{h^,}\,\left( x \right)\,\,using\,\,the\,\,product\,\,rule \hfill \\
\,\,{\left[ {uv} \right]^,} = u{v^,} + v{u^,} \hfill \\
Then \hfill \\
{h^,}\,\left( x \right)\, = = f\,\left( x \right){g^,}\,\left( x \right) + g\,\left( x \right){f^,}\,\left( x \right) \hfill \\
If\,\,x = 3 \hfill \\
{h^,}\,\left( x \right) = f\,\left( 3 \right){g^,}\,\left( 3 \right) + g\,\left( 3 \right){f^,}\,\left( 3 \right) \hfill \\
Substitute\,\,the\,\,given\,\,values \hfill \\
{h^,}\,\left( x \right) = \,\left( 9 \right)\,\left( 5 \right) + \,\left( 4 \right)\,\left( 8 \right) \hfill \\
Simplifying \hfill \\
{h^,}\,\left( 3 \right) = 45 + 32 \hfill \\
{h^,}\,\left( 3 \right) = 77 \hfill \\
\end{gathered} \]